1999
DOI: 10.1055/s-1999-41
|View full text |Cite
|
Sign up to set email alerts
|

Management of Duodenal Adenomas in 98 Patients with Familial Adenomatous Polyposis

Abstract: Duodenal adenomas almost invariably occur in FAP; endoscopic surveillance is thus warranted to anticipate severe progression and malignant transformation. Excisional surgical treatment can, however, give only transient stage reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 18 publications
4
93
1
5
Order By: Relevance
“…According to the Western reports, duodenal adenomas can be found in 30-70% of FAP patients and the lifetime risk of these lesions approaches 100%. 20 The incidence of duodenal cancer is rare, about 0.01-0.04% in general population, 21 but FAP patients have a 100-330 fold higher risk of duodenal cancer compared with the general population. 16 Bülow et al 15 reported the cumulative risk of developing duodenal cancer in FAP is about 4.5% at age of 57.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Western reports, duodenal adenomas can be found in 30-70% of FAP patients and the lifetime risk of these lesions approaches 100%. 20 The incidence of duodenal cancer is rare, about 0.01-0.04% in general population, 21 but FAP patients have a 100-330 fold higher risk of duodenal cancer compared with the general population. 16 Bülow et al 15 reported the cumulative risk of developing duodenal cancer in FAP is about 4.5% at age of 57.…”
Section: Discussionmentioning
confidence: 99%
“…Die operative Duodenotomie und Polypektomie kann wegen der hohen Rezidivrate nicht empfohlen werden [321,322]. Prinzipiell lässt sich auch nach extensivem chirurgischem Vorgehen das Wiederauftreten von Adenomen nicht verhindern [321].…”
Section: Level Of Evidence 1cunclassified
“…Surgical treatments including ampullectomy, duodenectomy, and pancreatico-duodenectomy appear effective for cancer prevention but are associated with significant procedureassociated risks (7,11). Medical treatment using the cyclooxygenase (COX) inhibitors sulindac and celecoxib has proven less effective in the duodenum than the colorectum (12)(13)(14)(15), but a recent trail of combined COX and EGFR inhibition with sulindac and erlotinib demonstrated promising short-term effects on duodenal polyp burden (16).…”
Section: Introductionmentioning
confidence: 99%